Diode lasers: A magical wand to an orthodontic practice - Vipul Kumar Srivastava; Shally Mahajan (Wolters Kluwer Medknow Publications, 2014)
LASER (Light Amplification by Stimulated Emission of Radiation) is a powerful source of light, which has innumerable applications in all the fields of science including medicine and dentistry. It is one such technology that has become a desirable and an inseparable alternative to many traditional surgical procedures being held in the field of dentistry, and orthodontics is no exception. The current article describes the uses of a diode laser as an indispensable tool in an orthodontic office.